Cyanoglobule lipid droplet accumulation as a stress response to nitrogen starvation in a non-N2-fixing mutant strain of Anabaena sp. PCC 7120 - Febri A. Susanto; Carrie Hiser; Mohit Mahey; Peter K. Lundquist (PLoS ONE, 2026)
Cyanoglobules are lipid droplets of cyanobacteria that share compositional and functional features with plastoglobules of plant chloroplasts. However, their roles in stress physiology remain poorly defined, particularly in filamentous cyanobacteria. Here, we characterize cyanoglobule dynamics and composition during nitrogen starvation in a non-diazotrophic derivative of Anabaena sp. PCC 7120. This experimental context enables analysis of sustained nitrogen deprivation in vegetative cells without the transient and heterogeneous effects of heterocyst differentiation and nitrogenase activity, while recognizing that the strain does not represent wild-type physiology. Nitrogen starvation induced striking morphological remodeling, including increased cyanoglobule size and abundance. Proteomic analysis revealed a cyanoglobule proteome enriched in homologs of the plant plastoglobule proteome as well as other redox regulators and isoprenoid metabolism enzymes, pointing to roles in pigment turnover and stress adaptation. Lipidome profiling revealed high levels of plastoquinone derivatives and other prenyl-lipid species. Collectively, our findings establish cyanoglobules as dynamic and stress-responsive compartments associated with redox and lipid remodeling during nutrient limitation. By leveraging a non-diazotrophic and comparative analysis, we show that key features of cyanoglobule formation and composition are observed independently of heterocyst differentiation and parallel those described in other cyanobacterial species and plant plastoglobules.